2012
DOI: 10.5897/ajb12.321
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and assessment of genetic diversity of sorghum inbred lines

Abstract: Selecting parents of diverse genetic base with contrasting phenotype is an important step in developing mapping populations for quantitative trait loci (QTL) detection and marker-assisted selection. We studied genetic diversity in 31 sorghum parents using 413 sorghum simple sequence repeats (SSR) markers. The polymorphism information content (PIC), a measure of gene diversity, varied from 0 to 0.92 with an average of 0.53 and was significantly correlated with number of alleles. The primers IS10215, IS10270 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
7
1
Order By: Relevance
“…The Ethiopian sweet sorghum collections showed distinct clustering between accessions from the north and those from the eastern and west central Ethiopia. The results are in agreement with past studies conducted for Ethiopian (Beyene et al, 2014) and global sorghum collections (Madhusudhana et al, 2012;Ramu et al, 2013;Lekgari and Dweikat, 2014) in which clustering based on geographic origin was observed for both grain and sweet sorghum. Other studies that included different sorghum races (Wang et al, 2013) and assessed their biological status (Billot et al, 2013) further reported clustering based on geographic origin and race Wang et al, 2013;Kitavi et al, 2014) and also according to biological status (Billot et al, 2013).…”
Section: Pic N a R A C A A A P A N A R A C A A A P Asupporting
confidence: 93%
See 1 more Smart Citation
“…The Ethiopian sweet sorghum collections showed distinct clustering between accessions from the north and those from the eastern and west central Ethiopia. The results are in agreement with past studies conducted for Ethiopian (Beyene et al, 2014) and global sorghum collections (Madhusudhana et al, 2012;Ramu et al, 2013;Lekgari and Dweikat, 2014) in which clustering based on geographic origin was observed for both grain and sweet sorghum. Other studies that included different sorghum races (Wang et al, 2013) and assessed their biological status (Billot et al, 2013) further reported clustering based on geographic origin and race Wang et al, 2013;Kitavi et al, 2014) and also according to biological status (Billot et al, 2013).…”
Section: Pic N a R A C A A A P A N A R A C A A A P Asupporting
confidence: 93%
“…This is further confirmed by other studies that characterized Ethiopian sorghum accessions maintained in Ethiopia (Adugna, 2014) or elsewhere (Cuevas and Prom, 2013) as well as those from Kenya (Mutegi et al, 2011) that reported comparable proportions of rare alleles. Although an overall high level (78.7%) of rare alleles has been reported in global composite germplasm collection (GCGC) of sorghum (Billot et al, 2013), the proportion of rare alleles reported for Indian sorghum collections have been lower than in the current study (Madhusudhana et al, 2012). The Ethiopian sweet sorghum collections showed distinct clustering between accessions from the north and those from the eastern and west central Ethiopia.…”
Section: Pic N a R A C A A A P A N A R A C A A A P Acontrasting
confidence: 76%
“…This research could not only provide guidance for sorghum drought breeding, but also help the selection and cultivation of new genotypes of water stress tolerant sorghum. Greatly improving the potential application of marker-assisted selection (MAS) in sorghum improvement has been done (Wu and Haung, 2006;Madhusudhana et al, 2012). Generally, molecular marker in cereal breeding have been varied and include identification and fingerprinting of parental genotypes, assessing genetic diversity, detection of quantitative trait loci (QTL) and MAS with introgression of QTL into elite germplasm.…”
Section: Phylogenetic Treementioning
confidence: 99%
“…Due to the impact of sorghum as one of the most important cereal crops around the world, it is possible to find a wide number of studies related to determination of genetic diversity of this species (AKRAM et al, 2011;BAHAA et al, 2013;DAHLBERG, 2011;LEKGARI and DWEIKAT, 2014;MADHUSUDHANA et al, 2012;MBEYAGALA et al, 2012;MOFOKENG et al, 2012;RITTER et al, 2007). In this sense, the present study is aimed to assess the genetic diversity of sorghum genotypes from the Czech Plant Gene Bank, Crop Research Institute in Prague, through Random Amplified Polymorphic DNA molecular markers (RAPD).…”
Section: Introductionmentioning
confidence: 99%